Hexachlorobenzene alters cell cycle by regulating p27-cyclin E-CDK2 and c-Src-p27 protein complexes. (15th March 2017) - Ventura, C.; Núñez, M.; Gaido, V.; Pontillo, C.; Miret, N.; Randi, A.; Cocca, C.
Highlights: HCB is a persistent organochlorine pollutant that acts as endocrine disruptor. HCB alters cell cycle progression and cell cycle regulating proteins in estrogen-sensitive MCF-7 breast cancer cell line. Cell cycle alterations exerted by HCB are related to the modulation of cyclin E-CDK2 and c-Src-p27 protein complexes. Abstract: Hexachlorobenzene (HCB) is an organochlorine pollutant widely distributed in the environment around the entire world. Previous reports from our group and others have demonstrated that this compound is as an endocrine disruptor. We have also reported that HCB presents a co-carcinogenic effect in N-Nitroso-N-methyl-urea–induced mammary tumours in rats. In this work, we studied the effects of HCB on cell cycle progression and cell cycle regulating protein expression in the estrogen-sensitive breast cancer cell line, MCF-7. Here, we show that HCB alters cell cycle in a concentration-dependent way. The lowest assessed concentration (0.005 μM) promotes the cell cycle progression, enhances cyclin D1 expression, and reduces the nuclear localization of p27 accompanied by an increased interaction between p27 and c-Src kinase. On the other hand, 5 μM HCB delays the cell cycle progression and promotes the formation of the cyclin E-CDK2-p27 protein complex. Our results show that HCB stimulates cell proliferation through cell cycle modulation and c-Src involvement in MCF-7 cells. Here, we report for the first time that differential mechanisms of action of HCB on mammary cell cycle progression are triggered at different concentrations of this pollutant.